Respuesta :
u= 32 - 6y
u = 17 - 3y
Step 1
32 - 6y = 17 - 3y
Step 2
-6y + 3y = 17 - 32
Step 3
-3y = - 15
Step 4
3y = 15
Step 5
y = 15/3
Step 6
y = 5
u = 17 - 3y
Step 1
32 - 6y = 17 - 3y
Step 2
-6y + 3y = 17 - 32
Step 3
-3y = - 15
Step 4
3y = 15
Step 5
y = 15/3
Step 6
y = 5
U+6y=32 U+3y=17
Solve U+6y=32 for u
Add -6y to both sides
U+6y-6y=32-6y U= -6y+32
Substitute -6y+32 for U in U+3y=17 U+3y=17 -6y+32+3y=17
Simplify both sides of the equation -3y+32=17
Add -32 to both sides -3y+32-32=17-32 -3y=-15
Divide both sides by -3 -3y/-3 = -15/-3 Y=5
Substitute 5 for y in U=-6y+32 U= -6y+32
U= (-6)(5)+32 u= -30 +32 U= 2
Answer : U= 2 and Y=5
I hope that's help and have a great night !